?SYNTHESIS OF SOME HYDRAZONE ANDPYRAZOLINE DERIVATIVES - FAIDALLAH, HASSANM.; MOKHTAR, HASSANM; NASSAR, AHMED; AHMED, MOHAMEDM (Biological Sciences - PJSIR, 1995)
Condensation of chalcones (I) with aroyl-and arylhydrazines afforded the corresponding hydrazones (2 and 3), cyclization of the hydrazones (3) with HCI gave the pyrazoline derivatives (4) which on oxidation with bromine water yielded the corresponding pyrazoles (5). Addition of 5-p-bromophenyl-3-methyl-l-p-sulphamylphcnylpyrazole (5c) to allylisothiocyanate afforded the thiourea derivative (6) which was readily cyclized with ethyl bromoacctatc to the corresponding oxothiazolidine (7).